Is drinking wine in moderation good for health or not? - Poli, Andrea (European heart journal supplements, 2022)
Drinking alcoholic beverages is associated with various health effects in the population. Generally speaking, the evidence from epidemiological studies suggest that moderate alcohol intake is associated with a reduction in the risk of cardiovascular events, such as myocardial infarction; the risk of cancer, on the other hand, tends to rise; whether an increase in the incidence of cancer is observed also in association with moderate consumption levels is yet not definitively ascertained. All these effects seem primarily to be associated with the amount of alcohol consumed; the role of the different alcoholic beverages, and of their minor components, in this regard is in fact not clearly defined. Due to the opposite direction of the association between alcohol consumption and cardiovascular and cancer events, the association with all-cause mortality is complex, and J-shaped, with a consumption window theoretically associated with a reduction in all-cause mortality, up to 25 g alcohol per day. However, this issue is the subject of intense scientific debate.